2010
DOI: 10.1021/nl9038778
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Interference Channeling at Graphene Edges

Abstract: Electron scattering at graphene edges is expected to make a crucial contribution to the electron transport in graphene nanodevices by producing quantum interferences. Atomic-scale scanning tunneling microscopy (STM) topographies of different edge structures of monolayer graphene show that the localization of the electronic density of states along the C-C bonds, a property unique to monolayer graphene, results in quantum interference patterns along the graphene carbon bond network, whose shapes depend only on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
129
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(148 citation statements)
references
References 35 publications
19
129
0
Order By: Relevance
“…superstructure has been reported in other experiments and always is related to armchair edges [23][24][25]. The (√3×√3)R30° periodicity of the interference pattern in the STM image can also be observed in the Fast Fourrier transform of the STM image ( Fig.…”
Section: Cnrs-laboratoire De Photonique Et De Nanostructures (Lpn)supporting
confidence: 78%
See 1 more Smart Citation
“…superstructure has been reported in other experiments and always is related to armchair edges [23][24][25]. The (√3×√3)R30° periodicity of the interference pattern in the STM image can also be observed in the Fast Fourrier transform of the STM image ( Fig.…”
Section: Cnrs-laboratoire De Photonique Et De Nanostructures (Lpn)supporting
confidence: 78%
“…3(b)): we identify a first group of spots corresponding to graphene reciprocal 4 lattice (RL) (the corresponding lattice parameter is about 0.23 nm) and a second set of spots reflecting the (√3×√3)R30° superstructure. Similar interference patterns are a strong indication of a structural discontinuity of the graphene lattice at the step since it is not observed when the graphene film grows continuously across the substrate step [22][23][24]26]. …”
Section: Cnrs-laboratoire De Photonique Et De Nanostructures (Lpn)mentioning
confidence: 79%
“…We emphasize that a few publications have tried so far to give a description of the different features in the experimental FT-LDOS images of epitaxial graphene. 27,28,30,31 However, a poor resolution in k space was partly limiting such analysis. In a report published in 2008, some of us have shown that it was possible to evidence fine structures in FT-LDOS data with improved quality.…”
Section: High-resolution Stm Results On Monolayer Graphene On Sicmentioning
confidence: 99%
“…[27][28][29][30][31][32][34][35][36][37][38][39][40][41][42] Because of the topology of the FS pockets, coupling between states with opposite q F in each pocket [ Fig. 1(d)] is highly favored.…”
Section: Quasiparticle Scattering In Graphene: Intravalley and Imentioning
confidence: 99%
“…Nanometer-scale STM measurements, yielding both local density of states (LDOS) and topographic details, are extensively used both theoretically [9][10][11][12][13][14][15][16] and experimentally [17][18][19][20][21][22] in the study of graphene. However, the STM measures only local properties, whereas we often want to obtain information about the transport properties for electrons traversing the sample.…”
Section: Introductionmentioning
confidence: 99%